Effects of Water Quality on Reeling Performance and Raw Silk Quality of Silkworm (Br-Urboshi) Cocoons: Water of Bholahat Region - Munsur Rahman, M. (Asian Journal of Chemistry, 2010)
For many years raw silk output of Bholahat area of Nawabganj district has been becoming the highest. At present it is about 70% of Bangladesh's total raw silk production. It would be helpful to know the influence of water on raw silk for existing reeling centres and also while setting up new reeling centres for achieving better results. An attempt has been made in this study to assess the effect of these chemical constituents of available natural water collected from different sources in the traditional silk reeling areas of Bholahat on the reeling performance and quality. Four different water samples of Bholahat region together with distilled water were used to reel silk cocoons of the race (Br-Urboshi) and their effects on raw silk and silk quality were analysed. The results obtained and discussed herein suggest that water from bore-well and river water which contain relatively low hardness (total, temporary and permanent hardness) and low pH values with acceptable limit for silk reeling produced significantly more raw silk and better reelability, renditta, medium size deviation, tenacity and better winding breaks and cohesion.